Regulation of fruit firmness, maturity and quality of late maturing cultivars of peach with preharvest application of ReTain TM - Singh, Zora; Kennison, K.; Agrez, V. (International Society for Horticultural Science, 2003)
To test the efficacy of time of application of ReTain TM on fruit maturity, firmness, colour development and fruit quality of peach (Prunus persica), experiments were conducted at Pickering Brook and Bickley in Western Australia during 1999 and 2000. An aqueous solution containing a wetting agent ABG-7011 (0.1%) and ReTain TM @ 125g a.i. ha-1 (equivalent to 830 g ReTain TM ha-1) was sprayed onto trees 15, 10 or 5 days before the anticipated harvest date. These treatments were applied to 'O'Henry' and 'Summerset' during 1999 and 'Zee Lady' and 'Elegant Lady' during 2000. The results of these trials showed that a ReTain TM application to peach extended the harvesting period and delayed fruit maturity in 'O'Henry' and 'Summerset'. ReTain TM treatment 5-10 days before harvest also increased fruit firmness, total soluble solids, and acid content in both cultivars. Fruit colour development (red colour on yellow background) in 'O'Henry' and 'Summerset' was not affected with ReTain TM treatment. ReTain TM application also increased fruit firmness in 'Zee Lady' and 'Elegant Lady'. In 'Elegant Lady', ReTain TM showed no effects on fruit colour development during the first picking, but it reduced fruit colour during the second picking. Conversely, in 'Zee Lady', ReTain TM reduced fruit colour development during the first picking and had no effect during the second pick. In conclusion, application of ReTain TM 5 - 10 days before harvest proved more effective than at 15 days before harvest in improving fruit firmness and quality of late maturing cultivars of peach.